The Role of Employee Engagement in Bridging The Role Of Leadership To Work Discipline - Bahtiar Sulistyan, Riza; Aziz Safii, Abdul; Murtini (Bulletin of Management and Business, 2024)
In this study, conducted at PT Chery Indonesia and PT Handal Indonesia Motor, the relationship between Employee Engagement, Leadership, and Work Discipline in the Automotive sector was investigated. Leadership's pivotal role in enhancing employee engagement, which subsequently influences work discipline, was emphasized. Employee engagement also acts as a mediator between leadership and work discipline. Employing a quantitative approach, data analysis was done using Smart PLS, aiming to provide insights for productivity and service quality enhancement in the automotive sector. The research aimed to evaluate Leadership's Impact on Work Discipline and the role of Employee Engagement. All permanent employees at both companies were included in the study, utilizing non-probability sampling with saturated sampling and a total of 73 respondents. Findings revealed leadership's indirect influence on work discipline but a significant positive impact on employee engagement. Moreover, employee engagement positively affected work discipline, suggesting its mediating role between leadership and work discipline. Enhancing leadership may thus improve employee engagement, thereby bolstering work discipline.